Short-Run and Long-Run Determinants of Inflation Dynamics in the Visegrád Countries - Kjosevski, Jordan (Ekonomika, 2025)
This study investigates inflation dynamics in the Visegrád countries – specifically, Poland, Hungary, Czechia, and Slovakia – by using the Mean Group estimator for 2000–2023. Results show a strong long-run link between the wage growth and inflation, as a rising purchasing power fuels consumption. Global price factors significantly drive local inflation, underscoring vulnerability to external shocks, particularly amid geopolitical tensions like the Ukraine war. Government consumption, however, helps moderate inflation over time, suggesting that productive public spending can stabilize prices. In the short run, wage growth still impacts inflation – yet less intensely, while reflecting gradual price adjustments. The Ukraine conflict highlights persistent uncertainties influencing expectations. Policymakers should align wage policies with productivity gains and monitor external price pressures closely. Overall, the study provides insights into the ways how domestic and global factors interact to shape inflation in the Visegrád region, informing debates on economic stability and policy responses in Central and Eastern Europe.